Peningkatan Keterampilan Batik Organik dengan Pewarna Alami Lokal Plus Ekstrak Rumput Laut, di Desa Tosari Kecamatan Tosari Kabupaten Pasuruan - Saati, Elfi Anis; Siskawardani, Devi Dwi; jamroji, Jamroji (Universitas Tribhuwana Tunggadewi Malang, 2025)
Pasuruan Regency has become a tourist destination due to its high natural potential and the inspiration for its distinctive Batik motifs. KUBA (Komunitas Berkaidah Amanah) artisans are among the artisans who have persisted in developing Batik. The Segiri motif is a type of selected flora, becoming a specialty of their product, Segiri Batik. Currently, KUBA-Batik Segiri is engaged in its business in Pasuruan and already has an extensive marketing network, is passing on its branding experience to Tosarian Batik in Tosari Village and District, which is also trying to utilize local natural pigments (datto flowers, strawberry leaves) as its batik dyes. This is hampered by weak color pigments and a relatively long process, because it is a natural dye. The use of pigments results in a higher price. So, it is necessary to modify the mordanting to help improve the stability of its natural color, namely by using seaweed extract as a coloring adhesive. Tosarian batik makers develop typical Tengger/Bromo motifs and udeng. Community service is carried out by socializing the understanding of Pigments Alginates, and their functions. Then, there was a socialization session on